The influence of criminal career on the manner of perpetrating street robbery - Banović Božidar (University of Belgrade - Faculty of Law, Belgrade & Institute of Comparative Law, Belgrade, 2021)
Street development is a form of development and content of all elements of a significant criminal offense and was committed against one or more persons, who walked, known or unknown to the executor, performed in public places that should become proposed, parks, public garages, entrances and stairs in residential buildings, etc.). They belong to the more frequent types of robbery, characterized by less sophistication in execution and direct confrontation that determines the quantity of fear suffered, the scope and intensity of the studied consequences. The aim of the research was to examine the influence of the previous experience of the perpetrators of the robbery on the way of choosing the victim, the place of victimization and the presence of other persons who would be in the immediate or close environment of the street robbery victim. The sample consisted of 42 respondents who committed street robbery out of 120 examined perpetrators of the crime of robbery and serious cases of robbery and robbery, who were serving a prison sentence in the penitentiary in Sremska Mitrovica. Data were collected through an anonymous survey. The results show that there will be differences in the approach to victim first choice, place of execution, internal and external presence of others, between executor who have already and those who have no previous experience in development research. The executors of robbery who have already committed this act are not more inclined to type a potential victim, but they would rather decide to immediately commit a street robbery by encountering a victim with whom the "prey" is visually noticeable. When choosing the place where the crime was committed, they are more inclined to emphasize the possibility of safe removal, but they are more inclined to say that when they commit the crime at night, it will still be in a place that is not lit. Experience predisposes them to pay less attention to the external presence of other persons, while perpetrators who commit robbery for the first time give priority to victimization when the victim is alone. Proper understanding of these indicators can contribute to the qualitative improvement of the analysis, which will facilitate our identification of key starting points in the selection of the best solutions for effective intervention, in order to reduce street robberies.